Future Tourism Trends Volume 2 - (:unkn) unknown (Emerald Publishing Limited, 2024)
The world is entering a new technological age in which great changes are expected in all areas of human interest, life, and activity. These changes have been brought on by past and present man-made events, which have had both positive and negative consequences. Learn how AI, service robots, and voice control will affect tourism.